Analisis Profitabilitas Dan Leverage Dalam Menilai Tax Avoidance Pada PT. Indofood Suskes Makmur Tbk Periode 2016 - 2020 - Viola Marsela; Edison Hamid (STIE Jambatan Bulan, 2022)
This study aims to determine how profitability and leverage in assessing tax avoidance. The object of this research is PT. Indofood Sukses Makmur Tbk taken from the financial statements of 5 (five) years in the period 2016 - 2020. The calculation results show that the average Return On Assets for 5 (five) years in the period 2016 - 2020 is 5.78% per year as a whole categorized as good. And for the average Debt to Equity Ratio for 5 (five) years in the 2016 - 2020 period, which is 90% per year. And for the average Cash Effective Tax Rate for 5 (five) years in the 2016 - 2020 period, which is 34.29% per year, overall it is categorized as very good, when viewed from the industry standard, which is above 25%. Furthermore, according to the calculation that profitability and leverage in assessing tax avoidance for 5 (five) years in the 2016 - 2020 period, the result is a contribution of 6.01% and others are influenced by other factors that are not discussed and examined in this study.